Revisiting phage tail spike architecture: evidence for undetected receptor-binding proteins in Caudoviricetes with non-contractile tails - Matusiak, Rafał; Antczak, Magdalena; Kawa, Anna; Paszkiewicz, Małgorzata; Witaszewska, Jolanta; Kazimierczak, Joanna; Wójcik, Ewelina A. (Frontiers in Microbiology, 2025)
IntroductionBacteriophages, viruses that infect bacterial cells, have garnered renewed interest as potential therapeutic agents due to the growing threat of antibiotic resistance. Effective application of bacteriophages requires a comprehensive understanding of their structure and mechanisms of action. Recent advances in structural biology techniques, such as cryo-electron microscopy (Cryo-EM) and cryo-electron tomography (Cryo-ET), along with significant progress in genome sequencing and bioinformatics, have greatly enhanced our knowledge of bacteriophage biology. However, these techniques remain insufficient in some cases to fully resolve the structure and function of phage tail spikes and tail fibers.MethodsThis study investigates the receptor-binding proteins (RBPs) of bacteriophages within the Caudoviricetes family, which recognise various receptors on bacterial surfaces. Bioinformatic analysis involving protein complex modelling with AlphaFold2-Multimer and molecular dynamics simulations was employed to reveal the evolutionary conservation and structural diversity of RBPs across different phage genera.ResultsOur findings indicate that phages from the genera Dhillonvirus, Traversvirus, and Littlefixvirus lack a receptor-binding domain at the distal end of the central tail spike. Furthermore, we identified and reconstructed previously unannotated or misannotated proteins that may contribute to receptor recognition.DiscussionThese results suggest that the analysed phages possess an additional, previously unidentified protein at the tip of the tail spike, which likely facilitates interaction with receptor proteins on the bacterial cell surface.